Retention: it's all about respect - McGuire, Maureen; Houser, Janet; Jarrar, Thafer; Moy, Wendy; Wall, Michelle (The health care manager, 2003)
Retention of employees is often overlooked in developing strategies to deal with worker shortages in health care. Managers mistake requests for more money as the key indicator of job satisfaction. This article examines research conducted by three health service administration graduate students who looked at reasons staff were leaving their jobs or their occupations. Using three different research tools, the students found that job satisfaction is not all about money, or even benefits. Respect, recognition, and organizational commitment are what employees want in their jobs. The article describes the research methods used in the studies and the similarities in results.